Global chlorophyll distribution induced by mesoscale eddies - Zhao, Dandan; Xu, Yongsheng; Zhang, Xiangguang; Huang, Chao (Remote sensing of environment, 2021)
While mesoscale eddies can trap and transport chlorophyll (CHL) within the water columns, satellite measurements can only observe CHL at the sea surface. Here, we estimate the eddy-induced CHL distribution based on satellite observations, Argo float measurements, and global empirical models. The combination of satellite altimeter data and Argo measurements is used to detect eddy boundaries by tracking the outermost closed contours of potential vorticity (PV) at depth; then, sea surface CHL from satellite observations, together with their vertical distributions estimated from models are used to derive the CHL within eddy boundaries. We find that the CHL trapped by eddies can reach 3.2 × 1012g, which is about half of the total CHL in the ocean; the global time-mean CHL eddy-induced zonal transport adds up to 5.7 × 103 g/s westward. The results show that oceanic mesoscale eddies play an important role in the elevated CHL in the interior of the ocean. •The CHL trapped by eddies is quantified based on observed data and the model.•The eddy-trapped CHL is found to be about half of the total CHL in the ocean.•Eddies elevate CHL in the interior of the ocean.